I do not know at all I am sorry
12 1/2 because you do 5/6 x 15/1 which 6/3 equals 2 and 15/3 equals 5 so you do 5/2 x 5/1
Answer:
6(√2 - 5√3).
Step-by-step explanation:
3√2 ( 2 - 5 √6)
= 6√2 - 15√12
= 6√2 - 15√4√3
= 6√2 - 30√3
= 6(√2 - 5√3)
The answer to your math problem is C. The reason being is 2x times x is 2x^2 and 2x times 11 is 22x. So you first part of the problem looks like 2x^2+22. Then -6 times x is -6x and -6 times 11 is -66. So now the problem is 2x^2+22x-6x-66. So your answer after solving it is 2x^2+16x-66.